Modeling phase equilibria for a water-CO2-hydrocarbon mixture using CPA equation of state in CO2 injection EOR-storage processes: a Colombian case study - Juan David Aristizábal Marulanda; Cristiam David Cundar Paredes; Christian David Guerrero Benavides; Andres Aguirre; Juan Andres Pasos; Ivan Dario Moncayo Riascos; Marco Ruiz; Pedro Nel Benjumea Hernández; William Mauricio Agudelo; Raúl Osorio Gallego (CT&F Ciencia, Tecnología & Futuro)
Currently, it is necessary to reduce CO2 emissions into the atmosphere. The oil industry in Colombia can contribute through CO2 injection processes in depleted fields. To achieve this, it is essential to have knowledge of the physicochemical interactions of CO2 with reservoir fluids. To integrate CO2, water and hydrocarbon phases, advanced models are required that capture the phenomenology of thermodynamic equilibrium. The CPA (Cubic-Plus-Association) equation of state is an equation that adds an associative term to model the interaction of water with the hydrocarbon and CO2 phase.